A polyester catalyst activated by 2,5-furandicarboxylic acid and its preparation method and application

By using silica gel-supported metal complex based on 2,5-furandicarboxylic acid activation as a catalyst, the problems of few types of catalytic systems, complicated steps and poor results in the prior art are solved, and the synthesis of 2,5-furandicarboxylic acid polyester with high intrinsic viscosity and good hue are achieved.

CN116478386BActive Publication Date: 2025-04-04ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202211525567.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-04-04
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

In the prior art, there are few types of catalytic systems used to synthesize 2,5-furandicarboxylate polyester, complex preparation steps, and poor catalytic effect, resulting in low viscosity and poor hue of the polyester.

Method used

The silica gel-supported metal complex MxLy@SiO2 based on 2,5-furandicarboxylic acid activation was used as the polyester catalyst. After activation in the polymerization system, the catalyst can catalyze the copolymerization of 2,5-furandicarboxylic acid and diol with high selective effect to form a 2,5-furandicarboxylic acid polyester with high intrinsic viscosity number and good hue.

Benefits of technology

The polyester catalyst has achieved strong stability, high selectivity, high activity, and green-friendly. The 2,5-furandicarboxylate polyester has high intrinsic viscosity and good hue, which is suitable for a variety of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116478386B_ABST
    Figure CN116478386B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of polyesters, and discloses a polyester catalyst activated by 2,5-furandicarboxylic acid, and a preparation method and application thereof. The polyester catalyst of the present invention is a silica gel-supported metal complex M x L y @SiO2; wherein: M is the central metal, L is the ligand ion, and M and L are loaded on a silica gel carrier. The polyester catalyst of the present invention cannot catalyze the copolymerization of non-furanyl dicarboxylic acid and diol when it exists alone. When 2,5-furandicarboxylic acid exists in the polymerization system, it can catalyze the synthesis of PEF or 2,5-furandicarboxylic acid-based copolyester. It is speculated that 2,5-furandicarboxylic acid plays a role in activating the catalyst during the reaction. The polyester catalyst of the present invention has strong stability, high selectivity, high activity, is green and friendly, and the prepared 2,5-furandicarboxylic acid-based polyester has a high intrinsic viscosity and good hue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyester, and in particular to a polyester catalyst activated based on 2,5-furandicarboxylic acid, and a preparation method and application thereof. Background Art

[0002] Bio-based polyester uses renewable resources as the main raw material. While reducing the consumption of petroleum resources, it also reduces the pollution to the environment during the production of petroleum-based raw materials. It has the dual effects of saving petroleum resources and protecting the environment. Therefore, the development of high-performance bio-based polyester is in line with the concept of green environmental protection and energy saving. Polyethylene 2,5-furandicarboxylate (PEF) synthesized from biological 2,5-furandicarboxylic acid and ethylene glycol is superior to polyethylene terephthalate (PET) in terms of gas barrier properties, heat resistance, antistatic properties, etc. It is a bio-based polyester with excellent comprehensive performance and huge application potential. However, 2,5-furandicarboxylic acid is prone to side reactions such as decarboxylation under high temperature conditions, resulting in 2,5-furandicarboxylic acid-based polyesters facing problems such as low viscosity and yellow hue. Therefore, optimizing the polymerization process or designing a new catalytic system to obtain 2,5-furandicarboxylic acid-based polyesters with high intrinsic viscosity and excellent hue is the direction and goal of the majority of scientific and technological workers.

[0003] In the prior art of synthesizing furandicarboxylic acid-based polyesters, for example, patent document CN 102453242 B discloses a method for preparing 2,5-furandicarboxylic acid-based polyesters by direct esterification polymerization, wherein 2,5-furandicarboxylic acid reacts with a low-carbon diol under the action of a catalyst, and a high-quality polyfurandicarboxylic acid ester is formed through direct esterification and polymerization reaction, and then purification and separation. The steps of the method are complicated, and the purification of the crude polyester product will generate waste liquid and pollute the environment.

[0004] Patent document CN 102516513 B discloses a method for preparing a low-yellowing 2,5-furandicarboxylic acid-based polyester, which uses solution polymerization to obtain a white powdery 2,5-furandicarboxylic acid-based polyester under mild reaction conditions. This method can avoid the yellowing of polyester caused by aging and degradation due to melt polycondensation, but the solution polymerization production cost is high, the solvent recovery is difficult, and the molecular weight of the obtained polymer is low.

[0005] Patent document CN 106243331 B discloses a method for preparing polyethylene furandicarboxylate, which uses a nitrogen-containing catalyst with good stability to prepare a colorless or light-colored polymer. However, the catalyst preparation process involves a loading process and is relatively complicated.

[0006] Patent document CN 107098875 B discloses a method for preparing polyfurandicarboxylic acid diol ester, firstly synthesizing furandicarboxylic acid diol monomethyl ester, and then using furandicarboxylic acid diol monomethyl ester as a monomer raw material to synthesize non-yellowing furandicarboxylic acid-based polyester, the steps are complicated and the production cost is increased.

[0007] Patent document CN 108727575 B discloses a method for preparing a bio-based 2,5-furandicarboxylic acid-based copolyester, wherein an ester generated by the reaction of a dibasic acid, an aliphatic diol with 2,5-furandicarboxylic acid and a titanium silicon cobalt composite catalyst are uniformly mixed and reacted in sequence to obtain a bio-based 2,5-furandicarboxylic acid-based copolyester. As a Class 2B carcinogen, cobalt element has certain toxicity to living organisms.

[0008] Patent document CN 109810248 B discloses a furandicarboxylic acid copolyester and a preparation method thereof. The furandicarboxylic acid copolyester with excellent hue can be prepared by copolymerizing furandicarboxylic acid / furandicarboxylic acid ester, cyclohexanedimethanol and other diols and polyols having a hydroxyl number greater than or equal to 3 using one of an antimony-based catalyst, a germanium-based catalyst and a tin-based catalyst as a catalyst system. The antimony-based catalyst in the catalyst system will cause serious environmental pollution problems, and the chain extension effect formed by the polyol increases the technical difficulty in the production process.

[0009] Patent document CN 111269405 A discloses a method for preparing bio-based polyester with suppressed discoloration, that is, by lowering the esterification temperature and avoiding the decarboxylation side reaction of 2,5-furandicarboxylic acid, the hue of furandicarboxylic acid-based polyester is improved. The process of lowering the esterification temperature will sacrifice the esterification rate, and ultimately lead to a decrease in production efficiency.

[0010] The paper reported that Zhou Guangyuan and others from the Dalian Institute of Chemical Physics, Chinese Academy of Sciences, used elemental zinc as a catalyst and adopted the transesterification method to synthesize polyethylene 2,5-furandicarboxylate with excellent hue. The intrinsic viscosity of the obtained polyester was 0.68 dL / g. Compared with the direct esterification method, the transesterification method has disadvantages such as cumbersome polymerization process and high toxicity of by-product methanol (J.IND.ENG.CHEM., 2021, 99, 422-430).

[0011] In summary, there are currently no patents or literature reports on environmentally friendly, easy-to-store, highly active, and highly selective catalytic systems that can be used to synthesize high intrinsic viscosity, colorless 2,5-furandicarboxylic acid-based polyesters by direct esterification. Summary of the invention

[0012] The present invention aims at the technical problems that the existing catalytic systems for synthesizing 2,5-furandicarboxylic acid-based polyesters have few types, complicated preparation steps, poor catalytic effects, and the like, and provides a polyester catalyst activated by 2,5-furandicarboxylic acid, and a preparation method and application thereof. The polyester catalyst of the present invention cannot catalyze the copolymerization of non-furan dicarboxylic acid and diol when it exists alone, but can catalyze the copolymerization of dicarboxylic acid and diol when 2,5-furandicarboxylic acid exists in the polymerization system, and 2,5-furandicarboxylic acid participates in the polymerization to form 2,5-furandicarboxylic acid-based polyester. The polyester catalyst synthesized and loaded by the present invention through double decomposition reaction has strong stability, high selectivity, high activity, is green and friendly, and the prepared 2,5-furandicarboxylic acid-based polyester has high intrinsic viscosity and good color.

[0013] The specific technical scheme of the present invention is:

[0014] In the first aspect, the present invention provides a polyester catalyst based on 2,5-furandicarboxylic acid activation, which is a silica gel supported metal complex M x L y @SiO2; where: M is the central metal, L is the ligand ion, and M and L are loaded on a silica gel carrier.

[0015] The team of the present invention found that the polyester catalyst of the present invention cannot catalyze the copolymerization of non-furan dicarboxylic acid and diol when it exists alone, but can catalyze the synthesis of PEF or 2,5-furan dicarboxylic acid-based copolyester when 2,5-furan dicarboxylic acid exists in the polymerization system. It is speculated that 2,5-furan dicarboxylic acid plays a role in activating the catalyst during the reaction. The polyester catalyst of the present invention has strong stability, high selectivity, high activity, is green and friendly, and the prepared 2,5-furan dicarboxylic acid-based polyester has high intrinsic viscosity and good color.

[0016] Specifically:

[0017] M is selected from K + , Ca 2+ Sc 3+ 、Ti 4+ 、V 3+ 、V 4+ 、V 5+ Cr 3+ , Mn 2+ , Mn 4+ , Fe 2+ , Fe 3+ 、Ni 2+ , Cu + , Cu 2+ 、Zn 2+ , Ga 3+ ,Ge 2+ ,Ge 4+ One or more of .

[0018] The present invention finds that the fourth period metal elements have moderate Lewis acidity compared with other period metal elements, which can maintain good polymerization activity and avoid excessive side reactions.

[0019] L is selected from one or more of oxygen ion, hydroxide ion, borate ion, formate ion, acetate ion, oxalate ion, hydrogen oxalate ion, carbonate ion, bicarbonate ion, nitrite ion, aluminosilicate ion, silicate ion, metasilicate ion, phosphate ion, phosphite ion, monohydrogen phosphate ion, dihydrogen phosphate ion, sulfate ion, hydrogen sulfate ion, sulfite ion, hydrogensulfite ion, thiosulfate ion, hypobromite ion, chlorite ion, hypochlorite ion, arsenate ion, arsenite ion, C1-C20 alkoxy group, and C1-C20 aryloxy group.

[0020] The present invention has found that oxygen element exhibits strong polarity, and the good coordination ability of oxygen-containing ligands can effectively assist metal ions in selectively catalyzing polymerization reactions.

[0021] Preferably, M is selected from V 3+ , Mn 2+ , Fe 2+ , Cu + ,Ge 2+ One or more of .

[0022] The present invention further found that metal ions with strong reducing properties exhibit excellent antioxidant effects and can assist antioxidants in avoiding high-temperature oxidation reactions caused by trace amounts of air during the reaction process.

[0023] Preferably, L is selected from one or more of oxygen ions, borate ions, acetate ions, hydrogen oxalate ions, and bicarbonate ions.

[0024] The present invention further found that the above ligand ions do not show oxidizing properties in the polyester reaction system.

[0025] In a second aspect, the present invention provides a method for preparing a polyester catalyst, comprising the following steps:

[0026] a) dissolving compound A containing M in good solvent A, adding silica gel, and ultrasonically treating to obtain a solution of compound A dispersed with silica gel.

[0027] b) According to the valence balance theory, weigh the corresponding amount of compound B containing L.

[0028] c) dissolving compound B containing L in good solvent B to obtain a compound B solution.

[0029] d) In an inert gas atmosphere, gradually add a solution of compound A dispersed with silica gel to a solution of compound B until the reaction system becomes neutral, concentrate the solvent and place in a low temperature environment for precipitation.

[0030] e) filtering, washing and vacuum drying to obtain the silica gel supported metal complex M x L y @SiO2.

[0031] Preferably, in step a), the good solvent A is selected from one or more of ethanol, water and petroleum ether.

[0032] Preferably, in step a), the amount of M is 8-12 mmol, and the amount of good solvent A is 80-200 mL.

[0033] Preferably, in step a), the particle size of the silica gel is 300-400 mesh.

[0034] Preferably, in step a), the amount of silica gel used is 5 to 20 equivalents relative to M.

[0035] Preferably, in step a), the ultrasonic treatment time is 1 to 3 hours.

[0036] Preferably, in step c), the good solvent B is selected from one or more of ethanol, water and petroleum ether.

[0037] Preferably, in step c), the amount of the good solvent B is 80-200 mL.

[0038] Preferably, in step d), the dropping speed is 1 to 3 mL / min.

[0039] Preferably, in step d), the solvent is concentrated to 50-100 mL and then placed in a -40-5°C environment for precipitation.

[0040] In a third aspect, the present invention provides a method for applying the above-mentioned polyester catalyst to the preparation of 2,5-furandicarboxylic acid-based polyester, comprising the following steps: placing 2,5-furandicarboxylic acid, other dibasic acids, diols, and 10 to 1000 ppm (based on the total mass of the reaction raw materials) of the catalyst in a polyester reactor, performing esterification under the protection of an inert gas, performing polycondensation under vacuum conditions after the esterification is complete, and discharging the material after the polycondensation is completed to obtain 2,5-furandicarboxylic acid-based polyester.

[0041] When the polyester catalyst of the present invention is applied to the synthesis of 2,5-furandicarboxylic acid, the catalyst forms an active center with 2,5-furandicarboxylic acid in the esterification stage for high-selective catalytic polycondensation reaction, which not only maintains the characteristics of high activity, but also effectively avoids side reactions during the polymerization process. 2,5-furandicarboxylic acid participates in the polymerization reaction after activating the catalyst to form 2,5-furandicarboxylic acid-based polyester. The 2,5-furandicarboxylic acid-based polyester obtained by the above method has a number average molecular weight of 0.1×10 4 ~30×10 4 Da, intrinsic viscosity is 0.5-1.5 dL / g, L value>50, b value<20, and glass transition temperature is 0-200°C.

[0042] Preferably, the molar ratio of the diol to all dibasic acids is 1.0 to 3.0:1.

[0043] Preferably, the diol has the following structure of general formula I:

[0044]

[0045] Wherein, R is selected from C2-C20 alkyl, C6-C20 aryl, C2-C20 alkoxy, C6-C20 aryloxy, C2-C20 alkylthio, C6-C20 arylthio, C2-C20 alkylamino, C6-C20 arylamino, C2-C20 alkylphosphino, C6-C20 arylphosphino;

[0046] Preferably, the diol monomer (I) is a structure represented by A to X:

[0047]

[0048]

[0049] Preferably, the dibasic acid has the following structure of formula II:

[0050]

[0051] Among them, R' is selected from C2-C20 alkyl, C6-C20 aryl, C2-C20 alkoxy, C6-C20 aryloxy, C2-C20 alkylthio, C6-C20 arylthio, C2-C20 alkylamino, C6-C20 arylamino, C2-C20 alkylphosphino, C6-C20 arylphosphino.

[0052] Preferably, the dibasic acid monomer (II) is a structure represented by A' to X':

[0053]

[0054] Preferably, the esterification reaction temperature is 150-250° C. and the time is 0.25-5 h.

[0055] Preferably, the polycondensation reaction temperature is 200-300° C. and the reaction time is 0.5-10 h.

[0056] Preferably, a stabilizer and / or an antioxidant is added to the polyester reactor. The amount of the stabilizer is 10 to 1000 ppm (based on the total mass of the reaction raw materials); the amount of the antioxidant is 10 to 500 ppm (based on the total mass of the reaction raw materials).

[0057] Further, the stabilizer is a phosphorus compound; selected from one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, trimethyl phosphate, triethyl phosphate, triethyl phosphite, n-butyl phosphate, isopropyl phosphate, triphenyl phosphate, phenyl phosphoric acid, ethyl diphenyl phosphate, polyphenylphosphonic acid disulfone ester, phenylphosphonic acid-4-hydroxyphenyl ester, 2,4,6-trimethylbenzoylphenylphosphonic acid, 2-aminophenylphosphonic acid diisopropyl ester, dibutyl 2-hydroxyphenylphosphonate, dioctylphenyl phosphate, pentafluorophenyl diphenyl phosphate. Preferably, one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, trimethyl phosphate, and triethyl phosphate are selected.

[0058] Furthermore, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 1425, antioxidant 168, antioxidant 1790, and antioxidant 1098.

[0059] Compared with the prior art, the beneficial effects of the present invention are:

[0060] (1) The polyester catalyst of the present invention cannot catalyze the copolymerization of non-furanyl dibasic acid and diol when it exists alone. When 2,5-furandicarboxylic acid exists in the polymerization system, it can catalyze the copolymerization of dibasic acid and diol, and 2,5-furandicarboxylic acid participates in the polymerization to form 2,5-furandicarboxylic acid-based polyester. The polyester catalyst has strong stability, high selectivity, high activity, and is environmentally friendly.

[0061] (2) The 2,5-furandicarboxylic acid-based polyester prepared by the polyester catalyst of the present invention has a high intrinsic viscosity and good hue, and a number average molecular weight of 0.1×10 4 ~30×10 4 Da, intrinsic viscosity is 0.5-1.5 dL / g, L value>50, b value<20, and glass transition temperature is 0-200°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is a sample photo of polyethylene 2,5-furandicarboxylate (PEF) prepared in Example 1;

[0063] Figure 2 The hydrogen nuclear magnetic resonance spectrum of polyethylene 2,5-furandicarboxylate (PEF) prepared in Example 1;

[0064] Figure 3 The hydrogen nuclear magnetic resonance spectrum of poly (1,4-cyclohexanedimethanol 2,5-furandicarboxylate) (PECF) prepared in Example 2;

[0065] Figure 4 The hydrogen nuclear magnetic resonance spectrum of poly (ethylene 2,5-furandicarboxylate terephthalate) (PEFT) prepared in Example 2;

[0066] Figure 5 This is a sample photo of polyethylene 2,5-furandicarboxylate (PEF) prepared in Comparative Example 1. DETAILED DESCRIPTION

[0067] The present invention will be further described below in conjunction with the embodiments.

[0068] Overall embodiment

[0069] A polyester catalyst based on 2,5-furandicarboxylic acid activation, which is a silica gel-supported metal complex M x L y @SiO2; where: M is the central metal, L is the ligand ion, and M and L are loaded in the silica gel carrier. Specifically:

[0070] M is selected from K + , Ca 2+ Sc 3+ 、Ti 4+ 、V 3+ 、V 4+ 、V 5+ Cr 3+ , Mn 2+ , Mn 4+ , Fe 2+ , Fe 3+ 、Ni 2+ , Cu + , Cu 2+ 、Zn 2+ , Ga 3+ ,Ge 2+ ,Ge 4+ Preferably, M is selected from V 3+ , Mn 2+ , Fe 2+ , Cu + ,Ge 2+ One or more of .

[0071] L is selected from one or more of oxygen ions, hydroxide ions, borate ions, formate ions, acetate ions, oxalate ions, hydrogen oxalate ions, carbonate ions, bicarbonate ions, nitrite ions, aluminosilicate ions, silicate ions, metasilicate ions, phosphate ions, phosphite ions, monohydrogen phosphate ions, dihydrogen phosphate ions, sulfate ions, hydrogen sulfate ions, sulfite ions, hydrogensulfite ions, thiosulfate ions, hypobromite ions, chlorite ions, hypochlorite ions, arsenate ions, arsenite ions, C1-C20 alkoxy groups, and C1-C20 aryloxy groups. Preferably, L is selected from one or more of oxygen ions, borate ions, acetate ions, hydrogen oxalate ions, and bicarbonate ions.

[0072] A method for preparing a polyester catalyst comprises the following steps:

[0073] a) Dissolve compound A containing 8-12 mmol M in 80-200 mL good solvent A, add 300-400 mesh silica gel in an amount of 5-20 equivalents relative to M, and perform ultrasonic treatment for 1-3 hours to obtain a solution of compound A dispersed with silica gel. The good solvent A is selected from one or more of ethanol, water, and petroleum ether.

[0074] b) According to the valence balance theory, weigh the corresponding amount of compound B containing L.

[0075] c) dissolving the compound B containing L in 80-200 mL of a good solvent B to obtain a solution of the compound B. The good solvent B is selected from one or more of ethanol, water, and petroleum ether.

[0076] d) In an inert gas atmosphere, gradually dropwise add the compound A solution dispersed with silica gel into the compound B solution at a rate of 1 to 3 mL / min until the reaction system becomes neutral, concentrate the solvent to 50 to 100 mL, and place in an environment of -40 to 5°C for precipitation.

[0077] e) filtering, washing and vacuum drying to obtain the silica gel supported metal complex M x L y @SiO2.

[0078] A preparation method of 2,5-furandicarboxylic acid polyester comprises the following steps: placing 2,5-furandicarboxylic acid, other dibasic acids, diols, 10-1000 ppm (based on the total mass of the reaction raw materials) of a catalyst, 10-1000 ppm (based on the total mass of the reaction raw materials) of a stabilizer, and 10-500 ppm (based on the total mass of the reaction raw materials) of an antioxidant in a polyester reactor, esterifying at 150-250° C. for 0.25-5 h under the protection of an inert gas, polycondensing at 200-300° C. for 0.5-10 h under vacuum conditions after the esterification is complete, and discharging the material after the polycondensation is completed to obtain 2,5-furandicarboxylic acid polyester. The molar ratio of diols to the alcohol acid of all dibasic acids is 1.0-3.0:1.

[0079] The diol has the following general formula I:

[0080]

[0081] Wherein, R is selected from C2-C20 alkyl, C6-C20 aryl, C2-C20 alkoxy, C6-C20 aryloxy, C2-C20 alkylthio, C6-C20 arylthio, C2-C20 alkylamino, C6-C20 arylamino, C2-C20 alkylphosphino, C6-C20 arylphosphino; preferably, the diol monomer (I) is a structure shown by A-X:

[0082]

[0083] The dibasic acid has the following structure of Formula II:

[0084]

[0085] Among them, R' is selected from C2-C20 alkyl, C6-C20 aryl, C2-C20 alkoxy, C6-C20 aryloxy, C2-C20 alkylthio, C6-C20 arylthio, C2-C20 alkylamino, C6-C20 arylamino, C2-C20 alkylphosphino, C6-C20 arylphosphino.

[0086] Preferably, the dibasic acid monomer (II) is a structure represented by A' to X':

[0087]

[0088] The stabilizer is a phosphorus compound; selected from one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, trimethyl phosphate, triethyl phosphate, triethyl phosphite, n-butyl phosphate, isopropyl phosphate, triphenyl phosphate, phenyl phosphoric acid, ethyl diphenyl phosphate, polyphenylphosphonic acid disulfone ester, phenylphosphonic acid-4-hydroxyphenyl ester, 2,4,6-trimethylbenzoylphenylphosphonic acid, 2-aminophenylphosphonic acid diisopropyl ester, dibutyl 2-hydroxyphenylphosphonate, dioctylphenyl phosphate, pentafluorophenyl diphenyl phosphate. Preferably, it is one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, trimethyl phosphate, and triethyl phosphate.

[0089] The antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 1425, antioxidant 168, antioxidant 1790, and antioxidant 1098.

[0090] Example 1

[0091] Preparation of polyester catalyst:

[0092] 5 mmol FeCl2 and 5 mmol GeCl2 were dissolved in 80 mL pure water, 6 g 300 mesh silica gel was added, and ultrasonic treatment was performed for 2 h to obtain a FeCl2·GeCl2 aqueous solution dispersed with silica gel.

[0093] According to the valence balance theory, weigh 20 mmol NaHCO3 and dissolve it in 80 mL pure water.

[0094] In a nitrogen atmosphere, FeCl2 aqueous solution dispersed with silica gel was gradually added dropwise to NaHCO3 solution at a dropping rate of 2 mL / min until the reaction system became neutral. The solvent was concentrated to 50 mL and then placed in an environment at 5°C for precipitation.

[0095] After filtering, washing and vacuum drying, the silica gel-supported metal complex Fe(HCO3)2·Ge(HCO3)2@SiO2 was obtained.

[0096] Polyester Synthesis:

[0097] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 312g of 2,5-furandicarboxylic acid, 198g of ethylene glycol, 500ppm of Fe(HCO3)2·Ge(HCO3)2@SiO2, 50ppm of phosphoric acid, and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 210°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 230°C for 3h to obtain polyethylene 2,5-furandicarboxylate.

[0098] from Figure 1 It can be seen that colorless polyethylene 2,5-furandicarboxylate was obtained in this example.

[0099] Example 2

[0100] Preparation of polyester catalyst:

[0101] Dissolve 10 mmol of Cu28O4 in 80 mL of pure water, add 6 g of 300-mesh silica gel, and treat with ultrasound for 2 h to obtain a Cu2SO4 aqueous solution dispersed with silica gel.

[0102] According to the valence balance theory, weigh 20mmol NaHC2O4 and dissolve it in 100mL pure water.

[0103] In a nitrogen atmosphere, a Cu2SO4 aqueous solution dispersed with silica gel was gradually added dropwise to the NaHC2O4 solution at a dropping rate of 2 mL / min until the reaction system became neutral. The solvent was concentrated to 50 mL and then placed in an environment at 5°C for precipitation.

[0104] After filtering, washing and vacuum drying, the silica gel-supported metal complex CuHC2O4@SiO2 is obtained.

[0105] Polyester Synthesis:

[0106] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 496g of ethylene glycol, 50ppm of CuHC2O4@SiO2, 50ppm of phosphoric acid, and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 210°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 235°C for 2h to obtain polyethylene 2,5-furandicarboxylate.

[0107] from Figure 2 It can be seen that the polyethylene 2,5-furandicarboxylate obtained in this example can be clearly characterized by hydrogen nuclear magnetic resonance spectrum.

[0108] Example 3

[0109] Preparation of polyester catalyst:

[0110] 5 mmol FeCl2 and 5 mmol GeCl2 were dissolved in 80 mL pure water, 3 g 300 mesh silica gel was added, and ultrasonic treatment was performed for 3 h to obtain a FeCl2·GeCl2 aqueous solution dispersed with silica gel.

[0111] According to the valence balance theory, 20 mmol CH3COONa was weighed and dissolved in 80 mL pure water.

[0112] In a nitrogen atmosphere, FeCl2·GeCl2 aqueous solution dispersed with silica gel was gradually added dropwise to the CH3COONa solution at a dropping rate of 3 mL / min until the reaction system became neutral. The solvent was concentrated to 50 mL and then placed in an environment at 5°C for precipitation.

[0113] After filtering, washing and vacuum drying, the silica gel-supported metal complex Fe(CH3COO)2·Ge(CH3COO)2@SiO2 was obtained.

[0114] Polyester Synthesis:

[0115] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 396g of ethylene glycol, 10ppm of Fe(CH3COO)2·Ge(CH3COO)2@SiO2, 50ppm of triphenyl phosphate and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 220°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 230°C for 3h to obtain polyethylene 2,5-furandicarboxylate.

[0116] Example 4

[0117] Preparation of polyester catalyst:

[0118] 10 mmol of VCl3 was dissolved in 80 mL of pure water, 3 g of 300-mesh silica gel was added, and ultrasonic treatment was performed for 2 h to obtain a VCl3 aqueous solution dispersed with silica gel.

[0119] According to the valence balance theory, 30 mmol CH3COONa was weighed and dissolved in 80 mL pure water.

[0120] In a nitrogen atmosphere, VCl3 aqueous solution dispersed with silica gel was gradually added dropwise to the CH3COONa solution at a dropping rate of 3 mL / min until the reaction system became neutral. The solvent was concentrated to 50 mL and then placed in an environment at 5°C for precipitation.

[0121] After filtering, washing and vacuum drying, the silica gel-supported metal complex V(CH3COO)3@SiO2 was obtained.

[0122] Polyester Synthesis:

[0123] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 396g of ethylene glycol, 50ppm of V(CH3COO)3@SiO2, 50ppm of triphenyl phosphate and 100ppm of antioxidant 1076 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 220°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 240°C for 3h to obtain polyethylene 2,5-furandicarboxylate.

[0124] Example 5

[0125] Preparation of polyester catalyst:

[0126] 5 mmol Ca(CH3CH2O)2 and 5 mmol Fe(CH3CH2O)2 were dissolved in 100 mL ethanol, 6 g 300 mesh silica gel was added, and ultrasonic treatment was performed for 2 h to obtain a Ca(CH3CH2O)2·Fe(CH3CH2O)2 ethanol solution dispersed with silica gel.

[0127] According to the valence balance theory, 20 mmol of C6H5ONa was weighed and dissolved in 50 mL of ethanol.

[0128] In a nitrogen atmosphere, Ca(CH3CH2O)2 ethanol solution dispersed with silica gel was gradually added dropwise to the C6H5ONa solution at a dropping rate of 2 mL / min until the reaction system became neutral. The solvent was concentrated to 30 mL and then placed in a -20°C environment for precipitation.

[0129] After filtering, washing and vacuum drying, the silica gel supported metal complex Ca(C6H5O)2·Fe(C6H5O)2@SiO2 was obtained.

[0130] Polyester Synthesis:

[0131] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 396g of ethylene glycol, 100ppm of Ca(C6H5O)2·Fe(C6H5O)2@SiO2, 50ppm of triphenyl phosphate and 100ppm of antioxidant 1076 were added to the reactor. The feed port was closed, and the process of filling with nitrogen to 2 atmospheres and exhausting to 1 atmosphere was repeated three times. Stirring was started and the temperature was gradually raised to 210°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 230°C for 2h to obtain polyethylene 2,5-furandicarboxylate.

[0132] Example 6

[0133] Preparation of polyester catalyst: same as Example 3.

[0134] Polyester Synthesis:

[0135] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 396g of ethylene glycol, 50ppm of Fe(CH3COO)2·Ge(CH3COO)2@SiO2, 50ppm of triphenyl phosphate and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 220°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 240°C for 1h to obtain polyethylene 2,5-furandicarboxylate.

[0136] Example 7

[0137] Preparation of polyester catalyst: same as Example 3.

[0138] Polyester Synthesis:

[0139] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 396g of ethylene glycol, 50ppm of Fe(CH3COO)2·Ge(CH3COO)2@SiO2, 100ppm of trimethyl phosphate and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 220°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 230°C for 3h to obtain polyethylene 2,5-furandicarboxylate.

[0140] Example 8

[0141] Preparation of polyester catalyst: same as Example 5.

[0142] Polyester Synthesis:

[0143] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 496g of ethylene glycol, 50ppm of Ca(C6H5O)2·Fe(C6H5O)2@SiO2, 50ppm of phosphoric acid, and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 210°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 240°C for 2h to obtain polyethylene 2,5-furandicarboxylate.

[0144] Example 9

[0145] Preparation of polyester catalyst: same as Example 1.

[0146] Polyester Synthesis:

[0147] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 624g of 2,5-furandicarboxylic acid, 277g of ethylene glycol, 276g of 1,4-cyclohexanedimethanol, 100ppm of Fe(HCO3)2·Ge(HCO3)2@SiO2, 50ppm of triphenyl phosphate and 100ppm of antioxidant 1076 were added to the reactor. The feed port was closed, and the process of filling with nitrogen to 2 atmospheres and exhausting to 1 atmosphere was repeated three times. Stirring was started and the temperature was gradually raised to 220°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to flow out. After the water flow was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 230°C for 2h to obtain poly(2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol) ester.

[0148] from Figure 3 It can be seen that the poly (2,5-furandicarboxylic acid-1,4-cyclohexanedimethanol-ethylene glycol) ester obtained in this example can be clearly characterized by nuclear magnetic resonance hydrogen spectrum.

[0149] Example 10

[0150] Preparation of polyester catalyst: same as Example 1.

[0151] Polyester Synthesis:

[0152] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 312g of 2,5-furandicarboxylic acid, 332g of terephthalic acid, 396g of ethylene glycol, 100ppm of Fe(HCO3)2·Ge(HCO3)2@SiO2, 50ppm of phosphoric acid and 100ppm of antioxidant 1524 were added to the reactor. The feed port was closed, and the process of filling with nitrogen to 2 atmospheres and exhausting to 1 atmosphere was repeated three times. Stirring was started and the temperature was gradually raised to 240°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 260°C for 2h to obtain poly(2,5-furandicarboxylic acid-terephthalic acid-ethylene glycol) ester.

[0153] from Figure 4 It can be seen that the poly (ethylene glycol-2,5-furandicarboxylate) obtained in this example can be clearly characterized by hydrogen nuclear magnetic resonance spectrum.

[0154] Comparative Example 1

[0155] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 312g of 2,5-furandicarboxylic acid, 198g of ethylene glycol, 50ppm of Ti(OnBu)4, 50ppm of phosphoric acid and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the nitrogen was filled to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 210°C for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa, and the material was discharged after polycondensation at 230°C for 3h to obtain polyethylene 2,5-furandicarboxylate.

[0156] from Figure 5 It can be seen that the polyethylene 2,5-furandicarboxylate obtained in this example is dark yellow.

[0157] Comparative Example 2

[0158] A 2.5L reactor was evacuated to 50Pa and filled with nitrogen. Under the protection of inert gas, 332g of terephthalic acid, 198g of ethylene glycol, 50ppm of Fe(HCO3)2·Ge(HCO3)2@SiO2, 50ppm of phosphoric acid and 50ppm of antioxidant 1010 were added to the reactor. The feed port was closed, and the pressure was filled with nitrogen to 2 atmospheres and vented to 1 atmosphere three times. Stirring was started and the temperature was gradually raised to 250℃ for esterification reaction. When the reaction system reached 4 atmospheres, water began to discharge. After the water discharge was completed, the reaction system was evacuated to 50Pa. After condensation at 270℃ for 3h, the material was discharged to obtain only a low-viscosity esterified liquid.

[0159] Performance Testing

[0160] The basic test data of the polyester samples obtained in each embodiment and comparative example are shown in the following table:

[0161] Table 1. Performance parameters of polyester samples obtained in various embodiments and comparative examples

[0162] Intrinsic viscosity (dL / g) Diethylene glycol (mol%) Terminal carboxyl group (mol%) b-value Example 1 0.65 1.8 14.5 5.1 Example 2 0.62 1.6 20.0 11.2 Example 3 0.71 2.5 16.7 9.8 Example 4 0.58 2.1 22.9 12.0 Example 5 0.62 2.1 10.9 11.8 Example 6 0.69 2.8 9.8 15.9 Example 7 0.55 1.9 19.8 7.8 Example 8 0.60 3.0 15.7 12.5 Example 9 0.68 1.8 12.5 6.2 Example 10 0.71 2.5 9.2 4.2 Comparative Example 1 0.68 2.3 16.8 25.8 Comparative Example 2 0.21 3.5 44.8 -

[0163] From the comparison of the data in the above table, it can be seen that the polyester samples prepared in Examples 1-10 have both high intrinsic viscosity and good hue (b value), while the polyester sample obtained in Comparative Example 1 using Ti(OnBu)4 has a higher intrinsic viscosity, but the product is dark yellow with poor hue. In Comparative Example 2, since the dibasic acid monomer does not contain 2,5-furandicarboxylic acid, the polyester catalyst cannot be activated, so only a low-viscosity esterification liquid is obtained.

[0164] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0165] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A polyester catalyst activated by 2,5-furandicarboxylic acid, characterized in that: Silica gel supported metal complex M x L y @SiO2; M is the central metal, L is the ligand ion, and M and L are loaded on the silica gel carrier; M and L are selected from the following combinations: M is Fe 2+ and Ge 2+ ; L is a bicarbonate ion; or M is Cu 2+ ; L is hydrogen oxalate ion; or M is Fe 2+ and Ge 2+ ; L is an acetate ion; or M is V 3+ ; L is an acetate ion; or M is Ca 2+ and Fe 2+ ; L is C6H5O - ; The values ​​of x and y satisfy the valence balance of M and L.

2. A method for preparing a polyester catalyst as claimed in claim 1, characterized in that The following steps are involved: a) dissolving compound A containing M in good solvent A, adding silica gel, and ultrasonically treating to obtain a solution of compound A dispersed with silica gel; b) Weigh a corresponding amount of compound B containing L according to the valence balance theory; c) dissolving compound B containing L in good solvent B to obtain a solution of compound B; d) In an inert gas atmosphere, gradually dropwise add a solution of compound A dispersed with silica gel into a solution of compound B until the reaction system becomes neutral, concentrate the solvent, and place in an environment of -40 to 5° C. for precipitation; e) filtering, washing and vacuum drying to obtain the silica gel supported metal complex M x L y @SiO2.

3. The preparation method according to claim 2, characterized in that: In step a), The good solvent A is selected from one or more of ethanol, water, and petroleum ether; The dosage of M is 8-12 mmol, and the dosage of good solvent A is 80-200 mL; The particle size of the silica gel is 300-400 mesh; The amount of silica gel used is 5 to 20 equivalents relative to M; The ultrasonic treatment time is 1 to 3 hours.

4. The preparation method according to claim 2, characterized in that: In step c), The good solvent B is selected from one or more of ethanol, water and petroleum ether; The usage of the good solvent B is 80-200 mL.

5. The preparation method according to claim 2, characterized in that: In step d), The drop rate is 1-3 mL / min; The solvent was concentrated to 50-100 mL and then placed in a -40-5°C environment for precipitation.

6. Use of the polyester catalyst according to claim 1 or the polyester catalyst obtained by the preparation method according to any one of claims 2 to 5 in the preparation of 2,5-furandicarboxylic acid-based polyester.

7. A method for preparing 2,5-furandicarboxylic acid-based polyester using the polyester catalyst according to claim 1 or the polyester catalyst obtained by the preparation method according to any one of claims 2 to 5, characterized in that The method comprises the following steps: placing 2,5-furandicarboxylic acid, other dibasic acids, diols and 10-1000 ppm of a catalyst in a polyester reaction kettle, carrying out esterification under the protection of an inert gas, carrying out polycondensation under vacuum conditions after the esterification is complete, and discharging the material after the polycondensation is completed to obtain 2,5-furandicarboxylic acid-based polyester.

8. The preparation method according to claim 7, characterized in that: The molar ratio of the diol to all dibasic acids is 1.0 to 3.0:

1.

9. The preparation method according to claim 7, characterized in that: The diol has the following general formula I: Among them, R is selected from C2-C20 alkyl, C6-C20 aryl, C2-C20 alkoxy, C6-C20 aryloxy, C2-C20 alkylthio, C6-C20 arylthio, C2-C20 alkylamino, C6-C20 arylamino, C2-C20 alkylphosphino, C6-C20 arylphosphino.

10. The preparation method according to claim 7, characterized in that: The dibasic acid has the following structure of general formula II: Among them, R' is selected from C2-C20 alkyl, C6-C20 aryl, C2-C20 alkoxy, C6-C20 aryloxy, C2-C20 alkylthio, C6-C20 arylthio, C2-C20 alkylamino, C6-C20 arylamino, C2-C20 alkylphosphino, C6-C20 arylphosphino.

Citation Information

Patent Citations

  • Method for preparing oligofuran dioctyl phthalate ester by directly esterifying and polymerizing

    CN102453242B

  • Preparation method of low-yellowing 2,5-furandicarboxylic acid-based polyester

    CN102516513B

  • A method for preparing polyethylene furanate dicarboxylate

    CN106243331B

  • A method for preparing polyfuran dicarboxylate

    CN107098875B

  • A method for preparing a bio-based 2,5-furandicarboxylic acid copolyester

    CN108727575B